Development of Cultural Literacy Based Learning Design with Successive Approximation Model - Nadia Putri Kharismawati; Cepi Riyana (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to develop a culture-based learning design by applying the Successive Approximation Model (SAM) as an iterative approach that can create an inclusive and adaptive learning experience according to the cultural context of the learners. The SAM model was chosen for its ability to facilitate the flexible development of teaching materials through continuous cycles of evaluation and revision, ensuring the content's relevance to local cultural values, such as traditional wisdom, arts, and social practices closely tied to students' lives. The research method used was a mixed-methods approach, involving arts and culture teachers in Sumedang Regency as the primary respondents. Data was collected through closed questionnaires, and interviews. This study analyzes quantitative data from questionnaires using descriptive statistics, and qualitative data from interviews, observations, and documentation through the stages of data reduction, presentation, and conclusion drawing. The results showed that the application of the SAM model could enhance students' understanding of both local and other cultures, while also developing their awareness of the importance of cultural diversity. The iterative process in SAM allows for the development of more flexible and responsive teaching materials that meet students' needs, thus creating more meaningful learning experiences. This study contributes to the design of culture-based learning that is more relevant to the social and cultural developments in the global society.